2015
DOI: 10.1039/c5nr04827c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of hydrangea flower-like hierarchical gold nanostructures with tunable surface topographies for single-particle surface-enhanced Raman scattering

Abstract: The physicochemical properties of noble metal nanocrystals depend strongly on their size and shape, and it is becoming clear that the design and facile synthesis of particular nanostructures with tailored shape and size is especially important. Herein a novel class of hydrangea flower-like hierarchical gold nanostructures with tunable surface topographies and optical properties are prepared for the first time by a facile, one-pot, seedless synthesis using ascorbic acid (AA) to reduce hydrogen tetrachloroaurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…4a). 10 It is identied the intensity ratios of the (200) and (111) planes, I (200) /I (111) , were 0.39 and 0.23 respectively for the particles prepared at 1.0 and 3.0 mM BSA, suggesting the (111) is the predominant lattice plane to direct the growth of Au nanoowers. 11 Enlarged TEM image indicated that the surface of the Au particle prepared with 1.0 mM BSA was quite smooth (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…4a). 10 It is identied the intensity ratios of the (200) and (111) planes, I (200) /I (111) , were 0.39 and 0.23 respectively for the particles prepared at 1.0 and 3.0 mM BSA, suggesting the (111) is the predominant lattice plane to direct the growth of Au nanoowers. 11 Enlarged TEM image indicated that the surface of the Au particle prepared with 1.0 mM BSA was quite smooth (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…[6][7][8] A general strategy to synthesize Au NFs is to carry out the growth of Au nanoparticles (NPs) in the presence of shape-directing agents, which can preferentially adsorb onto specic crystal planes and thus direct the anisotropic growth of NPs along the uncapped facets. A variety of agents, such as surfactants, 9,10 polymers, 11 and biomolecules with active groups that allow their anchoring onto the specic planes, 12 have been proven to be effective to direct the growth of Au NFs. However, it is documented that Au NFs are readily to go ripening and become spherical in shape, especially in presence of chloride ions and/or under acidic pH.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of reaction conditions, such as growth temperature, precursor, and surfactant, were comprehensively studied to illustrate the growth mechanism of noble metals [30]. We investigated the influence of etching time on GNF to understand the 8 formation of flower-like Pt nanostructures.…”
Section: Characterization Of Flower-like Pt Npsmentioning
confidence: 99%
“…However, few studies have been conducted specifically on the preparation of highly SERS-active gold shell on the magnetic nanoparticles [24][25][26][27][28], and mainly partially gold coated rough shell or fully coated smooth shell have been prepared for SERS-based detections, which limits the application of MNPs@Au in the field of SERS. According to the SERS mechanism rough surface with nanoscale gaps or tips can generate stronger localized surface plasmon resonance (LSPR) compared with the smooth ones [29][30][31]. Though many gold nanoparticles with branched tips, such as tadpole- [32], star- [33], and urchin-shaped [34], were synthesized with enhanced SERS activities, few researches have been carried on the growth of branched gold shell on the magnetic cores with improved SERS performance.…”
Section: Introductionmentioning
confidence: 99%